Repertórios sobre crimes de feminicídio no jornal Folha de S. Paulo - Delavi, Marluci (2019)
The main objective of this research is to understand the repertoires used by the Jornal Folha de S. Paulo when reporting crimes of feminicide in the period from January to December 2018. In order to reach the research objective, the theoretical-methodological approach of discursive psychology developed in the Nucleus of Studies on Discursive Practices in Daily Life: rights, risks and health (NUPRAD/PUC-SP) was used, this approach is part of a constructionist approach. At first, a news survey was carried out in the newspaper database using as a descriptor the term feminicide. Subsequently, the search was refined for crimes of feminicide published only in the printed journal - the focus of the research - in order to analyze the repertories employed by journalists to position the female victim of feminicide, the aggressor and the crime. In general, the results indicate that the repertoires used by journalists do not go deeper in the discussions about gender violence that culminates in the crime of feminicide, which gives the impression that the murder is an isolated case; in addition, the News report do not provide information about the Law of Feminicide, either they divulge channels for denouncing or supporting victims of violence